COGNITIVE PRESENCE DALAM PEMBELAJARAN BERBASIS MOOCS: STUDI KOMPARATIF ANTARA DOSEN DAN MAHASISWA DI ICE INSTITUTE - Titi Chandrawati; Fajar Arwadi; Afriani; Heni Safitri; Nur Hikmah; Laksmi Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the level of cognitive presence among lecturers and students in MOOCs-based online learning at ICE Institute using the Community of Inquiry (CoI) framework. The study employed a quantitative descriptive approach. The instrument was adapted from the CoI Survey and validated through expert judgment. The respondents consisted of 38 students and 10 lecturers who actively participated in courses at ICE Institute during the odd semester of 2024. The sampling technique used purposive sampling with the criterion that respondents had completed at least four weeks of lectures. Data were analyzed using descriptive percentage statistics and proportion difference tests. The results showed that 80% of lecturers were categorized as having a high level of cognitive presence, while only 50% of students reached a similar level. Furthermore, 47.3% of students were categorized at a moderate level and 2.7% at a low level. This 30% gap indicates differences in perception and cognitive capacity between lecturers and students. Lecturers were considered highly competent in designing learning activities based on critical reflection; however, students had not fully utilized these opportunities. The study recommends the need for pedagogical interventions such as cognitive scaffolding, collaborative project-based learning, and self-regulated learning training for MOOCs students.